Emilia Pardo Bazán, women and education. The Pedagogical Conference (1892) and the Chair of Literature (1916) - De Gabriel, Narciso (Historia y Memoria de la Educación, 2018)
Over the course of her career, Emilia Pardo Bazán always had a continuing concern for educational issues, particularly as they related to women. Her participation in the Hispano-Portuguese-American Pedagogical Conference (1892) marked a turning point in the way women’s education was seen in Spain. The first part of this article presents an analysis of her lecture, the ensuing discussions among the participants and the repercussions it had in the press. In the second part, we have focused on minister Julio Burell’s decision to institute a professorship of Modern Literature in Neo-Latin languages, which was designed for the Galician writer, in the doctoral programme of the School of Philosophy and Liberal Arts at the Central University (1916). The professorship was to be awarded by means of an extraordinary procedure as regulated in the Moyano Act, but the candidate did not receive the support of two of the three institutions called upon to decide: the Royal Spanish Academy and the School of Philosophy and Liberal Arts. The only vote in favour came from the Council of Public Instruction, where she was a member. Despite this resistance, the minister went ahead with the proposal and awarded Doña Emilia the professorship.